Development of Community Economic Potential through Soybean Commodities in Sidorukun hamlet, West Stabat Lama Village, Langkat Regency - Alvi Khaira; Muniruddin (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
Most of the people in Sidorukun Hamlet depend on their livelihoods through the soybean commodity business which is then produced into tempeh, tofu, soy milk and tempeh crackers. This research aims to find soybean commodity products that have the most potential in developing the community's economy, as well as ways to increase the selling power and quality of soybean commodity products. This research is descriptive research using a qualitative approach. Data collection techniques in this research were carried out through observation and interviews. There were 6 informants in this study. The soybean commodity with the most potential is tempeh crackers, due to its longer shelf life and flexibility in distribution. To increase selling power, this can be done through e-commerce, diversifying products and brand image. In improving product quality, producers must have high quality human resources and routine quality control.